[Rezension von: Crouch, Carly L., 1982-, Translating empire : Tell Fekheriyeh, deuteronomy, and the Akkadian treaty tradition] - Hagedorn, Anselm C. 1971-; Crouch, Carly L. 1982- (2020)
This is a learned book, not easy to read and understand for the uninitiated. Crouch and Hutton embark on a study of the thorny subject of translation in the ancient world, ‘especially with regard to translation of an officially produced text from Akkadian into one of the Northwest Semitic languages’ (p. 1). The textual evidence they choose comes from the bilingual inscriptions discovered at Tell Fekheriyeh (Fekh.; KAI 309). Their starting point is the scholarly consensus that the Akkadian version is the source text and the Aramaic is the translation. Rather than simply restating the consensus, Crouch and Hutton want to offer a better understanding how the translation was done. Following recent developments in cognitive models of translation and bilinguality they argue from the outset that ‘translated texts constitute a subset of bilingual behavior’ (p. 23). Crouch and Hutton define the theoretical model employed to uncover the strategies behind the process of transforming the Akkadian source text into Aramaic as ‘Optimal Translation’. The term is a fusion, recently proposed and applied by Hutton, of two approaches to grammar and linguistics: Descriptive Translation Studies and Optimality Theory. Both approaches rightly stress that translation styles are not ad hoc decisions but may be subjected to detailed and theoretically informed description and quantification. ‘Adequacy’ and ‘acceptability’ govern the translation process. Since such an approach assumes the equivalence of a translation to its source text, it can be argued that ‘a translation is the translator’s best-formed target text, in which all relevant constraints have been balanced optimally, with regard to their respective levels of violability and forcefulness within the cultural system for which the target text has been produced’ (p. 31). As someone who occasionally works as a translator, this reviewer is struck by how many of the constraints and norms uncovered and detailed by Crouch and Hutton one subconsciously employs in the quest for an acceptable translation.
Keywords: Rezension